Exposing the gaps in awareness, knowledge and estimation of risk for anal cancer in men who have sex with men living with HIV: a cross‐sectional survey in Australia. Issue 1 (30th March 2015) - Ong, Jason J; Chen, Marcus; Grulich, Andrew; Walker, Sandra; Temple‐Smith, Meredith; Bradshaw, Catriona; Garland, Suzanne M; Hillman, Richard; Templeton, David; Hocking, Jane; Eu, Beng; Tee, BK; et al.
Abstract : Introduction: The incidence of anal cancer is significantly higher in men who have sex with men (MSM) living with HIV when compared to the general population. We aimed to assess their awareness, knowledge and perceived level of personal risk for anal cancer to help inform educational strategies targeting this group. Methods: A cross‐sectional study of 327 HIV positive MSM in Melbourne, Australia, attending clinical settings (a sexual health centre, tertiary hospital HIV outpatients and high HIV caseload general practices) completed a written questionnaire in 2013/14. Poor knowledge was defined as those who had never heard of anal cancer, or scored 5 or less out of 10 in knowledge questions amongst those who reported ever hearing about anal cancer. Underestimation of risk was defined as considering themselves as having the same or lower risk for anal cancer compared to the general population. Results: Of 72% (95% confidence interval (CI): 67–77) who had heard of anal cancer, 47% (95% CI: 41–53) could not identify any risk factors for anal cancer. Of total men surveyed, 51% (95% CI: 46–57) underestimated their risk for anal cancer. Multivariate analysis showed that men who underestimated their risk were older (OR 1.04 (per year increase in age), 95% CI: 1.01–1.07), had poor anal cancer knowledge (OR 2.06, 95% CI: 1.21–3.51), and more likely to have ever had an anal examination (OR 2.41, 95% CI: 1.18–4.93). They were less likely to consult a physician if they had an anal abnormality (OR 0.54, 95% CI: 0.31–0.96), to have had receptive anal sex (OR 0.12, 95% CI: 0.02–0.59) or speak English at home (OR 0.28, 95% CI: 0.09–0.90). Conclusions: This survey of MSM living with HIV demonstrated limited awareness, knowledge level and estimation of risk for anal cancer. Further educational and public health initiatives are urgently needed to improve knowledge and understanding of anal cancer risk in MSM living with HIV.